EMPOWERMENT OF BUKIT PARIAMAN VILLAGE COMMUNITY IN MANAGING HOUSEHOLD ORGANIC WASTE INTO ECO ENZYME-BASED PRODUCTS TO IMPROVE ENVIRONMENTAL SANITATION - Enih Rosamah; Hastaniah Hastaniah; Marjenah Marjenah; Sri Asih Handayani; Jufriah Jufriah; Nani Husien (Jurnal Abdisci, 2025)
Abstract: Organic waste, perticularly from household remains, can be easily decomposed naturally without human intervention. When processed correctly and properly, organic waste from households offers many benefits, such as being converted into animal or livestock feed, organic fertilizer, compost, biogas, and eco enzyme. The nature of eco enzyme is an antimicrobial that inhibits pathogens, makes it useful as a cleaning agent. Community Service Activities involving approximately 15 RT (Neighborhood Associations) in Bukit Pariaman Village, Tenggarong Seberang District (especially to local houswives), provided training on making Eco Enzyme and the application of eco enzyme in daily life needs. In practice, eco enzyme is used as a multi-purpose cleaning fluid, including for detergent, air purifier, floor cleaner, toilet cleaner, kitchen cleaner, odor remover, dishwashing liquid, fruit and vegetable cleaner, hair and skin care, pesticides, insecticides. Eco enzyme is considered environmentally friendly because it is processed entirely from organic materials. The community service activities were successfully conducted and received enthusiasm from training participants who actively asked questions, engaged in discussions, and practiced making eco enzyme, and after a three-month fermentation period, they successfully produced eco enzyme products. Keywords: Eco Enzyme, Bukit Pariaman Village, Cleaning Agent